English Teachers and Autonomous Learning - Sofyan A. Gani; Zulfadli A. Aziz; Nurlayli Yanti (English Education Journal, 2017)
This study investigates the understanding and beliefs of Acehnese teachers concerning autonomous learning as mandated in the 2013 curriculum and how their beliefs about the concept of learner autonomy were applied in their teaching practices. The purposes of this research were: 1) to find out what is the understanding of English Foreign Language (EFL) teachers concerning autonomous learning, and 2) to find out howwell the EFL teachers performed at implementing autonomous learning as mandaited in the 2013 curriculum. The data was obtained by studying 4 EFL teachers from two different schools. It was collected in two phases of study, utilising both a quantitative method (a survey) and qualitative methods (interviews and observations). The instruments used for collecting the data were a questionnaire, interviews and field note observation. This study found that the teachers studied generally lacked understanding about learner autonomy and there were some inconsistencies between the  beliefs of the teachers’and their actual teaching practices regarding learner autonomy, as little evidence could be found that many students regarded themselves as autonomous learners in their studies. The findings from this study will hopefully provide teachers and policy-makers with new insights into fostering learner autonomy to improve the educational system in Indonesia especially in Aceh.